The social dynamics of the Muiscas neighborhood as determinants of health (2021)
Objective: To understand under the conception of the social determinants of health, aspects related to public spaces, sustainability, economy and internal conflicts of the Muiscas neighborhood of the city of Tunja (Boyacá), in the year 2019. Methodology: 8 visits to the neighborhood were made from September to November 2019; in which, through direct observation of the researchers, 24 field records were made; which allowed after systematizing the information, to select the categories of analysis. Results: The commercial area of the neighborhood has strengthened its microeconomics, thanks to the periphery that it presented at the beginning in relation to the center of the city of Tunja. On the other hand, green areas are places of recreation for their inhabitants, with the realization of activities, some recreational and others labeled as the consumption of substances, generating a feeling of insecurity at certain times of the day.